Immune control of Mycobacterium tuberculosis is dependent on both soluble TNFRp55 and soluble TNFRp75. Issue 3 (8th July 2021) - Keeton, Roanne; du Toit, Jan Pierre; Hsu, Nai‐Jen; Dube, Felix; Jacobs, Muazzam
Abstract: Tuberculosis presents a global health challenge, and tumour necrosis factor (TNF) signalling is required for host immunity against Mycobacterium tuberculosis ( Mtb ). TNF receptor shedding, however, compromises effective immunity by reducing bioactive TNF through the formation of inactive complexes. In this study, we first compared the effect of total soluble TNF receptors using a transgenic p55 ΔNS /p75 −/− murine strain on host protection during a low‐dose aerosol Mtb H37Rv challenge. We report that the presence of membrane‐bound TNFRp55 alone in the absence of TNFRp75 results in superior control of a primary Mtb infection where p55 ΔNS /p75 −/− hyperactive dendritic cells displayed an increased capacity to induce a hyperactive Mtb ‐specific CD4 + T‐cell response. p55 ΔNS /p75 −/− dendritic cells expressed a higher frequency of MHCII and increased MFIs for both CD86 and MHCII, while CD4 + T cells had higher expression of CD44 and IFN‐γ. Next, the relative contributions of soluble TNFRp55 and soluble TNFRp75 to host protection against either primary Mtb infection or during reactivation of latent tuberculosis were delineated by comparing the experimental outcomes of control C57BL/6 mice to transgenic p55 ΔNS /p75 −/−, p55 ΔNS and p75 −/− mouse strains. We found that soluble TNFRp55 is redundant for immune regulation during the chronic stages of a primary Mtb infection. However, TNFRp55 together with soluble TNFRp75 has a crucial role in immune regulation of reactivation of latent tuberculosis. Abstract : Tumour necrosis factor (TNF) signalling is required for host immunity against Mycobacterium tuberculosis (Mtb); however, TNF receptor shedding compromises effective immunity by reducing bioactive TNF through the formation of inactive complexes. Here, we show that soluble TNFRp55 is redundant for immune regulation during the chronic stages of a primary Mtb infection. However, TNFRp55 together with soluble TNFRp75 has a crucial role in immune regulation of reactivation of latent tuberculosis.